Оценка достоверности математических моделей в задачах высокоскоростного термокинетического деформирования элементов конструкций цилиндрической формы - Бизюк, А. В.; Чернобрывко, М. В.; Ярещенко, В. Г. (НТУ "ХПИ", 2001)
In work is done a comparative analysis of mathematical models of high-rate elasto-plastic deforming of cylindrical shells, which based on comparison with experimental data. An optimum model is a 2-dimension layer with taking into account deformation speed dominance and thermal parameters.
Keywords: упругопластическое деформирование; тензометрическая станция; величина деформации; скорость деформации; предел пластичности; температурные напряжения